2003
DOI: 10.1002/art.10697
|View full text |Cite
|
Sign up to set email alerts
|

Adalimumab, a fully human anti–tumor necrosis factor α monoclonal antibody, for the treatment of rheumatoid arthritis in patients taking concomitant methotrexate: The ARMADA trial

Abstract: Objective. To evaluate the efficacy and safety of adalimumab (D2E7), a fully human monoclonal tumor necrosis factor ␣ antibody, in combination with methotrexate (MTX) in patients with active rheumatoid arthritis (RA) despite treatment with MTX.Methods. In a 24-week, randomized, double-blind, placebo-controlled study, 271 patients with active RA were randomly assigned to receive injections of adalimumab (20 mg, 40 mg, or 80 mg subcutaneously) or placebo every other week while continuing to take their long-term … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

56
815
5
57

Year Published

2004
2004
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,609 publications
(933 citation statements)
references
References 19 publications
56
815
5
57
Order By: Relevance
“…The detection of antibodies is dependent on the patient population studied, the timing and frequency of serum sampling, and the sensitivity and specificity of the detection assay used. Thus, the reported incidence can vary greatly between studies of the same biologic agent (3,15,16). In the present study, we employed a sensitive assay to study antibody production both while patients were receiving study medication, as is typically reported for other products, and after a 20-week washout following the last study injection, when golimumab concentrations would likely be low enough to minimize interference with antibody detection.…”
Section: Discussionmentioning
confidence: 99%
“…The detection of antibodies is dependent on the patient population studied, the timing and frequency of serum sampling, and the sensitivity and specificity of the detection assay used. Thus, the reported incidence can vary greatly between studies of the same biologic agent (3,15,16). In the present study, we employed a sensitive assay to study antibody production both while patients were receiving study medication, as is typically reported for other products, and after a 20-week washout following the last study injection, when golimumab concentrations would likely be low enough to minimize interference with antibody detection.…”
Section: Discussionmentioning
confidence: 99%
“…Therapy with TNF␣ blocking agents has resulted in remarkable improvement in RA, both in clinical and radiologic parameters (59)(60)(61). In a recent study of RA patients with active disease at baseline, those with the TNFA -308 GG genotype responded better to infliximab (3 mg/kg) than did patients with AA or AG genotypes (33); 42% of patients in the AA plus AG group versus 81% of those in the GG group had improvement of at least 1.2 in the DAS28 score (28 joints assessed) (P ϭ 0.008).…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic strategies that have targeted individual pathophysiologic mediators, such as TNF␣ and IL-1, have produced significant clinical benefits for many, but not all, patients with RA (28)(29)(30)(31). Improved strategies may evolve from the combined targeting of more than one critical mediator of inflammation and destruction, or from upstream targeting at pivotal transcriptional levels.…”
Section: Discussionmentioning
confidence: 99%